Digital Shopping Behavior Transformation: The Influence of Shopee's Interactive Features on Impulsive Buying in Millennials and Gen Z - Mohamad Nur Singgih; Ratih Agustin Rahmaningrum; Rateh Faradina (Fundamental and Applied Management Journal, 2026)
The ease of shopping through e-commerce platforms has encouraged the emergence of consumer behavior among consumers known as impulsive buying. The study investigates how live streaming and flash sale and PayLater functions impact impulse buying among Shopee users who belong to millennial and Generation Z demographics. Data collection involved distributing questionnaires to 100 respondents who were selected through random sampling methods. The study employs quantitative research methods which use primary data for analysis through descriptive statistics testing and t-test and F test and determination coefficient test in SPSS software version 23. The study results demonstrate that live streaming and flash sale and PayLater functions all positively impact impulsive buying behavior. The three independent variables show that live streaming emerges as the most powerful factor which affects impulse buying behavior among millennial and Generation Z Shopee users.